Case Report: Transcatheter interventional procedure to innominate vein turn-down procedure for failing fontan circulation - Schaffner, Damien; Perez, Maria-Helena; Duran, Rafael; Pretre, René; Di Bernardo, Stefano (Frontiers in Pediatrics, 2024)
Fontan physiology creates a chronic state of decreased cardiac output and systemic venous congestion, leading to liver cirrhosis/malignancy, protein-losing enteropathy, chylothorax or plastic bronchitis. Creating a fenestration improves cardiac output and relieves some venous congestion. The anatomic connection of the thoracic duct to the subclavian-jugular vein junction exposes the lymphatic system to systemic venous hypertension and could induce plastic bronchitis. To address this complication, two techniques have been developed. A surgical method that decompresses the thoracic duct by diverting the innominate vein to the atrium, and a percutaneous endovascular procedure that uses a covered stent to create an extravascular connection between the innominate vein and the left atrium.We report a novel variant transcatheter intervention of the innominate vein turn-down procedure without creating an extravascular connection in a 39-month-old patient with failing Fontan circulation complicated by plastic bronchitis and a 2-year post-intervention follow-up.